2017
DOI: 10.5937/ekopolj1701323r
|View full text |Cite
|
Sign up to set email alerts
|

Measures to support the development of organic farming in the EU and Serbia

Abstract: Aim of this paper work is analyzing the situation in the sector

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Research from around the world shows that production based on the principles of organic farming gives lower yields than conventional agriculture (Schrama et al 2018). However, lower yields can be offset by numerous benefits, including increased soil fertility, stable production and high quality food, reduced pollution and protection of agroecosystems, income security and strengthening of local communities, and promotion of public health (Roljevic-Nikolic, Vukovic, and Grujic, 2017;Leifeld, 2012;Aldanondo-Ochoa, Casasnovas-Oliva, and Arandia-Miura, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from around the world shows that production based on the principles of organic farming gives lower yields than conventional agriculture (Schrama et al 2018). However, lower yields can be offset by numerous benefits, including increased soil fertility, stable production and high quality food, reduced pollution and protection of agroecosystems, income security and strengthening of local communities, and promotion of public health (Roljevic-Nikolic, Vukovic, and Grujic, 2017;Leifeld, 2012;Aldanondo-Ochoa, Casasnovas-Oliva, and Arandia-Miura, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organic production as an alternative production system, categorizes as sustainable agriculture with different environmental approaches, could be useful in conservation of biodiversity (Jevtić et al, 2020). Also, organic farming represents a comprehensive system of farm management and food production that protects environment, preserves biodiversity and natural resources (Roljević et al, 2017). The sustainability of organic production is reflected in the rational use of natural resources, without exhausting, but rather through maintaining and increasing their diversity, leaving no negative impacts on the environment (Roljević et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, organic farming represents a comprehensive system of farm management and food production that protects environment, preserves biodiversity and natural resources (Roljević et al, 2017). The sustainability of organic production is reflected in the rational use of natural resources, without exhausting, but rather through maintaining and increasing their diversity, leaving no negative impacts on the environment (Roljević et al, 2017). The best alternative for further expansion and development of organic agriculture is its integration into a global strategic framework such as the SDG as to connect various aspects of sustainable agriculture and stakeholders and to secure a pivotal position in healthy and safe food production while protecting the environment (Šeremešić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An important factor contributing to the growth of the organic sector is financial performance. Namely, in addition to the higher prices of organic products realized on the market, the strong growth of this sector is also encouraged by the financial support provided to organic producers by a large number of countries (Brožová, 2011;Roljević Nikolić et al, 2017). The results of a three-year examination of organic and conventional farms showed that organic farms mainly had greater profitability than conventional farms, but that this result was conditioned by subsidies (Brožová and Vaněk, 2013).…”
Section: Introductionmentioning
confidence: 99%